Parenting and Proximity to Social Services: Lessons from Los Angeles County in the Community Context of Child Neglect - Maguire-Jack, Kathryn (Child Abuse Negl, 2015)
Using a sample of 438 parents in Los Angeles County, CA, this study examines the role of proximity to social services in child neglect. In an extension of social disorganization theory, it seeks to understand the potential sources of support in neighborhoods for families. It uses ordinary least squares regression to examine driving distance from parents’ residences to four types of services (child care, domestic violence, mental health/substance abuse, and poverty). The results show an association between proximity to mental health and substance abuse services and parents’ self-reported neglectful behaviors. Additionally, higher levels of socioeconomic disadvantage (poverty, unemployment, and low education), having older children, respondents being male, and respondents being older parents are associated with higher levels of child neglect, while being white is associated with lower levels. Overall, the findings suggest a potentially protective role of geographic access to mental health and substance abuse services in child maltreatment. Additional research on the pathways through which proximity to services influences child neglect is needed.